2003
DOI: 10.1177/000992280304200405
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions in Breastfed Infants: Less Than Imagined

Abstract: Medication use during breastfeeding shortens the duration of breastfeeding often because of overly cautious information given by healthcare providers. No comprehensive review of the literature on infant adverse reactions from drugs in breastmilk has been published. All published studies and case reports on adverse events in infants caused by medications (excluding drugs of abuse) in breastmilk were identified and analyzed. Of 100 case reports evaluated, none were considered to be "definite" using a standard ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
15

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 101 publications
2
47
0
15
Order By: Relevance
“…71 In our previous article, 51% of cases involved CNS depressants, and in this study, they account for 69%. 1 Overall, of the 153 cases from our 2 reviews, 88 (58%) cases involved drugs with CNS activity. All deaths reported in this article and in our previous article involved one or more CNS depressants.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…71 In our previous article, 51% of cases involved CNS depressants, and in this study, they account for 69%. 1 Overall, of the 153 cases from our 2 reviews, 88 (58%) cases involved drugs with CNS activity. All deaths reported in this article and in our previous article involved one or more CNS depressants.…”
Section: Discussionmentioning
confidence: 88%
“…1 In this article, we used the same methodology to collect and assess case reports since 2002. We also reviewed studies designed to determine the frequency of adverse effects from specific drugs or drug classes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, unexplained apnea, bradycardia, cyanosis, and sedation have been reported in nursing infants of mothers receiving codeine. 2,66 Hydrocodone is also metabolized via the CYP2D6 pathway. On the basis of pharmacokinetic data, infants exposed to hydrocodone through human milk may receive up to 9% of the relative maternal dose.…”
Section: Pain Medicationsmentioning
confidence: 99%
“…The age of the infant is also an important factor in the decision-making process, because adverse events associated with drug exposure via lactation occur most often in neonates younger than 2 months and rarely in infants older than 6 months. 2 In the near future, pharmacogenetics may also provide important guidance for individualized decisions.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive review of the published literature on adverse reactions from maternal medications in breastfed infants found that 78% of published cases occurred in infants under 2 months of age and only 4% of published cases were in infants over 6 months of age. 9 Infants reported to have adverse reactions involving hydrocodone were 18 days and 5 weeks of age. 2,3 Similarly, the death from codeine and its metabolites in breast milk occurred in a 13-day-old infant.…”
Section: Discussionmentioning
confidence: 99%